Muscle contributions to take-off velocity in the long jump - Yang, K.; Tang, W.-T.; Liu, S.-H.; Pandy, M. G. (Medicine & Science in Sports & Exercise, 2023)
Purpose A key determinant of long jump performance is the ability to increase the vertical velocity of the center of mass (COM) while minimizing the loss in forward velocity (running speed) during the take-off phase, but exactly how this occurs is not fully understood. We combined a three-dimensional musculoskeletal model of the body with dynamic optimization theory to simulate the biomechanics of the long jump take-off and determine the contributions of the individual leg muscles to jump performance.